Gamma-ray detector based on high pressure xenon for radiation and environmental safety - Kutny, V.E.; Rybka, A.V.; Davydov, L.N.; Pudov, A.O.; Sokolov, S.A.; Kholomeyev, G.A.; Melnikov, S.I.; Turchin, A.A. (Вопросы атомной науки и техники, 2017)
Gamma-spectrometers based on compressed xenon gas assigned for monitoring the reactors and the radiation background at nuclear power plants, non-proliferation of radioactive materials, supervision and control over the radiation background in the environmentally disadvantaged areas, and other applications, are very promising detectors with excellent performance characteristics. This article reports on the results of the first stage of work on the creation of the portable γ-spectrometer based on compressed xenon that is unique for Ukraine. In order to work with ultra-pure gases under pressure, the complex cryogenic installation for Xe purification and detector filling was designed and manufactured. The installation was made of specially cleaned components, equipped with a heating system for the degassing of the inner walls, and is able of maintaining high vacuum down to 2∙10⁻⁹ mbar. A prototype ionization chamber for the use in portable HPXe detectors was developed and made. For the detector testing, a spectrometric channel based on high-quality electronic components was designed and manufactured. In the initial experiments, a study of the properties of the purified Xe mixed with the dopant H₂ was carried out. The assessment of the lifetime of charge carriers τ in the working gas at a pressure of 30 bar gave the value of τ > 150 μs. Гамма-спектрометри на основі стисненого газу ксенону, що призначені для спостереження і контролю за реакторами і навколишнім фоном на АЕС, нерозповсюдженням радіоактивних матеріалів, радіаційним фоном в екологічно несприятливих зонах і інших застосувань, є дуже перспективними детекторами з відмінними експлуатаційними характеристиками. Дана стаття присвячена результатам першої стадії роботи по створенню унікального для України переносного γ-спектрометра на основі стисненого ксенону. Для роботи з чистими газами під тиском розроблена і виготовлена комплексна кріогенна установка очищення і напуску Xe. Установка створена на основі особливо чистих комплектуючих, оснащена системою прогріву для дегазації внутрішніх стінок і здатна підтримувати високий вакуум до 2∙10⁻⁹ мбар. Розроблено та виготовлено прототип іонізаційний камери для використання в переносних HPXe-детекторах. Для роботи детекторів розроблений і виготовлений спектрометричний тракт на основі високоякісних електронних блоків. В якості перших випробувань проведені дослідження властивостей суміші очищеного Хе з легуючою домішкою H₂. При оцінці часу життя носіїв заряду τ в робочому газі під тиском 30 бар отримані значення τ > 150 мкс. Гамма-спектрометры на основе сжатого газа ксенона, предназначенные для наблюдения и контроля за реакторами и окружающим фоном на АЭС, нераспространением радиоактивных материалов, радиационным фоном в экологически неблагоприятных зонах и других применений, являются очень перспективными детекторами с отличными эксплуатационными характеристиками. Данная статья посвящена результатам первой стадии работы по созданию уникального для Украины переносного γ-спектрометра на основе сжатого ксенона. Для работы с чистыми газами под давлением разработана и изготовлена комплексная криогенная установка очистки и напуска Xe. Установка создана на основе особо чистых комплектующих, оснащена системой прогрева для дегазации внутренних стенок и способна поддерживать высокий вакуум до 2∙10⁻⁹ мбар. Разработан и изготовлен прототип ионизационной камеры для использования в переносных HPXe-детекторах. Для работы детекторов разработан и изготовлен спектрометрический тракт на основе высококачественных электронных блоков. В качестве первых испытаний проведены исследования свойств смеси очищенного Хе с легирующей добавкой H₂. При оценке времени жизни носителей заряда τ в рабочем газе под давлением 30 бар получены значения τ > 150 мкс.